PELATIHAN SPEAKING DAN LITERASI HUKUM KOMUNIKASI DI SMA NEGERI 27 BATAM: The Training of Speaking and Communication Law Literacy at SMA Negeri 27 Batam - Padrisan Jamba; Tomi Arianto; Afriana Afriana (PUAN INDONESIA, 2023)
In the world of work, many company need high school or bachelor graduates who have soft and hard skills. One of supporting soft skill needed in work world is the ability to communication. For this reason, students in school are expected to be able to understand communication literacy. Many are proficient in English but sometimes lack direction and lack knowledge of communication literacy. On this occasion, Putera Batam University lecturers conducted training activity for Students in high school on Profession English Proficiency and Communication Law Literacy especially at SMA Negeri 27 Batam. Lecturers who provide coaching and training are lecturers who are experts in their fields; they are from English Literature and Law program. The training provided is oriented towards improving language speaking skills and communication legal literacy using the communication practice method. The results of this training show that students are able to demonstrate their communication skills by 1) appearing in front of the class practicing their language skills 2) Understanding about communication literacy is shown by active participation of students in discussions 3) evaluating by holding practice followed by discussion.